Uji Kesukaan Minuman Boba Dengan Tambahan Buah Naga - Silfa Sofiatunnisa; Sulih Wahyudiono Sulih (LPPM and Travel Operation Department Universitas Asa Indonesia, 2024)
Boba drinks are one of the contemporary drinks that have recently emerged among Indonesian people. This drink contains tapioca balls mixed with milk, as well as additional brown sugar syrup or liquid brown sugar. In this research, an innovation will be carried out by adding dragon fruit to boba making, which aims to increase health awareness in an attractive and contemporary package. This research uses a hedonic test, to determine the level of respondents' preferences for color, aroma, texture and taste. The data collection technique used was a questionnaire given to 65 writers. From the questionnaire distribution data, 38% (25 panelists) said they liked the color. Then 48% (31 Panilis) said they liked the aroma. Then 42% (27 panelists) said they really liked the texture. And 43% (28 panelists) said they liked the taste. then together the authors got 98% answers (like answers) with a total of 254 answers and 2% (like answers) with a total of 11 answers. So it can be concluded that the